Chemical Composition and Acaricidal Activity of the Essential Oils of Some Plant Species of Lamiaceae and Myrtaceae against the Vector of Tropical Bovine Theileriosis: Hyalomma scupense (syn. Hyalomma detritum). (7th February 2019) - Djebir, Somia; Ksouri, Samir; Trigui, Mohamed; Tounsi, Slim; Boumaaza, Awatif; Hadef, Youssef; Benakhla, Ahmed
Abstract : The present study aimed to investigate the acaricidal properties of six essential oils. They were extracted from some plant species ( Lamiaceae and Myrtaceae ) using the technique of hydrodistillation with the Clevenger apparatus. The chemical compositions of the essential oils under study were determined by gas chromatography–mass spectrometer (GC-MS). An Adult Immersion Test (AIT) and a Larval Immersion Test (LIT) were used to evaluate the acaricidal activity of these essential oils against the adults and larvae of Hyalomma scupense . GC-MS analysis showed the major constituents of each essential oil: 25.49% of α -thujone (lavender); 46.82% of carvacrol (oregano); 78.78% of carvacrol (thyme); 40.27% of 1, 8-cineole (blue gum); 17.45% of p-cymene (river red gum); and 26.96% of 1, 8-cineole (rosemary). The biotests on the essential oils revealed that they inhibit the reproduction of H. scupense engorged females at a rate of 100 % with doses of 0.781  μ l/ml of rosemary, 1.562  μ l/ml of thyme, 3.125  μ l/ml of lavender and oregano, and 6.250  μ l/ml of blue gum and river red gum. After a treatment that lasted for 24 hours, essential oils showed a larvicidal activity with respective values of lethal concentrations (LC): LC50, LC90, and LC95 (0.058, 0.358, and 0.600  μ l/ml for thyme; 0.108, 0.495, and 0.761  μ l/ml for rosemary; 0.131, 0.982, and 1.740  μ l/ml for oregano; 0.155, 2.387, and 5.183  μ l/ml for blue gum; 0.207, 1.653, and 2.978  μ l/ml for river red gum; and 0.253, 2.212, and 4.092  μ l/ml for lavender). This is the first report on the acaricidal activity of these essential oils against H. scupense. The results obtained showed that the essential oils with chemotype carvacrol, 1, 8-cineole, α -thujone, and p-cymene are highly acaricidal, and they can be used for ticks control. However, further studies on their toxicity in nontarget organisms are required.